The Effect Of Core Training On The Balance Of Shooting Athletes In Banjarbaru City - Adinda Tri Maharani; Eka Purnama Indah; Akhmad Amirudin (UNIB Press, 2025)
Shooting requires a high level of concentration and balance of the body to maintain accuracy and stability when aiming at the target. Good balance is an important factor because athletes must maintain a fixed position for a long time. This study aims to analyze the effect of core training on the balance of shooting athletes in Banjarbaru City. The method used was pre-experiment with a pretest-posttest control group design. The population in this study is shooting athletes in the city of Banjarbaru which consists of 20 athletes. The sample in this study uses the total sampling technique, which uses the entire population. The sample of this study was divided into two groups, namely the treatment group that was given core training and the control group that underwent regular physical exercise. The instrument used is the standing stork test to measure balance. The results of the data analysis showed that the data was distributed normally and homogeneously. The paired t-test showed significant results (p < 0.05), indicates the influence of core training on balance that has never been applied to shooting athletes in the city of Banjarbaru.